Presbyopic spectacle coverage and barriers to near vision correction among adult population in ido local government area, Southwest Nigeria - Mukaila Alaba Seidu; Charles O Bekibele; Ayobade O Ayorinde (Journal of Clinical Sciences, 2017)
Background: The magnitude of presbyopes with appropriate near vision correction is low globally and spectacles' correction remains cost-effective option for low- and middle-income countries. Objectives: The objective of this study was to determine presbyopia correction coverage (PCC), presbyopic met need and unmet need, willingness to pay for a pair of near vision spectacles, and barriers to usage of near vision spectacles among adults aged 40 years and above in a semiurban population of Southwest Nigeria. Materials and Methods: A cross-sectional, population-based study was carried out on 440 participants who were 40 years and above. Participants were selected using multistage sampling technique. Participants had refraction for both distance and near vision. Information on the use, barriers, and source of near vision spectacle was collected using interviewer-administered questionnaire. Data analysis was done using Statistical Package for Social Sciences software version 22 (IBM Corp., New York, USA). Results: A total of 440 participants were examined. Male to female ratio was 1:1.2 and the mean age of the participants was 51 ± 8 years. The PCC in the study was 27.3% with met need of 20.5% and unmet need of 54.5%. The major barriers to usage of near spectacles in this study were “not a priority” at 38.4% (95% confidence interval [CI] 32.3–44.5) and “not aware of the problem” at 34.7% (95% CI 28.7–40.7). Most of the participants (75.7%) were willing to pay at least 1000 naira (US$6) for a pair of near spectacles; hence, cost was not a significant barrier. Conclusion: The PCC in the area was low. Basic eye screening and refractive services should be incorporated into primary eye care for easy accessibility by the adult population in this area.